Development of android based learning media on the subjects of digital photo composition for vocational high school student - Rini Sefriani; Indra Wijaya; Popi Radyuli (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
This study aims to develop an Android SmartPhone based learning media for Digital Photo Composition in Vocational High School. This research is a Research and Development, conducted in Vocational Secondary School class XI. The results of the assessment of the three validators overall validator test assessment of the Interactive Module of 88.00% so that the level of validity can be interpreted very Valid is used. Overall assessment of the practicality of learning media based SmartPhone Andorid as learning resources of 83.96%, so that practical level can be interpreted Practically used. And assessment of the effectiveness of learning media based Andorid SmartPhone as learning resources of 89.19%, so the level of effectiveness can be interpreted Very Effective use.